Nicotine and fluoxetine alter adolescent dopamine-mediated behaviors via 5-HT1A receptor activation - Yuan, Menglu; Leslie, Frances M. (Frontiers in Psychiatry, 2024)
Abuse or misuse of tobacco, e-cigarettes, or antidepressants may have serious clinical consequences during adolescence, a sensitive period during brain development when the distinct neurobiology of adolescent serotonin (5-HT) and dopamine (DA) systems create unique behavioral vulnerabilities to drugs of abuse. Using a pharmacological approach, we modeled the behavioral and neurochemical effects of subchronic (4-day) nicotine (60µg/kg, i.v.) or fluoxetine (1mg/kg, i.v.) exposure in adolescent and adult male rats. Nicotine and fluoxetine significantly enhance quinpiroleinduced locomotor activity and initial cocaine self-administration in adolescents, but not adults. These effects were blocked by serotonin 5-HT1A receptor antagonists, WAY-100,635 (100 µg/kg, i.v.) or S-15535 (300 µg/kg, i.v.). Given their different pharmacological profiles, comparison between WAY-100,635 and S-15535 indicates that postsynaptic 5-HT1A receptors mediate the behavioral effects of prior nicotine and fluoxetine exposure. Neurochemical and anatomical autoradiographic analysis of 8-OH-DPAT-stimulated [ 35 S]GTPγS reveal that prior exposure to nicotine and fluoxetine results in both overlapping and distinct effects on regional 5-HT1A receptor activity. Both fluoxetine and nicotine enhance adolescent 5-HT1A receptor activity in the primary motor cortex (M1), whereas fluoxetine alone targets prefrontal cortical neurocircuitry and nicotine alone targets the amygdala. Thus, within the adolescent M1, maladaptive changes in 5-HT signaling and 5-HT1A activity after nicotine or fluoxetine exposure may potentiate hyper-responsiveness to dopaminergic drugs and prime adolescent vulnerability for future substance abuse.